Pengembangan Sistem Informasi Alumni Berbasis Web SMK Negeri 1 Koto XI Tarusan - Melda Triyana Tanjung; Denny Kurniadi; Ahmaddul Hadi; Lativa Mursyida (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The alumni information system is an example of an information system specifically designed for the purpose of supporting the work of educational institutions, especially at SMK Negeri 1 Koto XI Tarusan, if you want to process alumni data and view all the data through web-based information services. At SMK Negeri 1 Koto Web-based alumni are very necessary to collect alumni data in a comprehensive and easily accessible manner. This research aims to design a web-based alumni information system using the waterfall development method which allows the development process to be carried out in stages starting from analysis, design, to implementation of the system. With this method, it is hoped that the system design can be more structured, efficient, and make it easier for schools to collect current alumni data.